Fall protection in construction - Herman, Alexis M., 1947- (U.S. Dept. of Labor, Occupational Safety and Health Administration, 1998)
In the construction industry in the U.S., falls are the leading cause of worker fatalities. Each year, on average, between 150 and 200 workers are killed and more than 100,000 are injured as a result of falls at construction sites. OSHA recognizes that accidents involving falls are generally complex events frequently involving a variety of factors. Consequently, the standard for fall protection deals with both the human and equipment-related issues in protecting workers from fall hazards. For example, employers and employees need to do the following: Where protection is required, select fall protection systems appropriate for given situations. Use proper construction and installation of safety systems. Supervise employees properly. Use safe work procedures. Train workers in the proper selection, use, and maintenance of fall protection systems.--